Radiation fields in moving media: new numerical and analytical solutions of the transfer equation - Wehrse, Rainer; Baschek, Bodo (Physics reports, 1999)
Significant progress has recently been achieved in the solution of the radiative transfer equation for various geometries, velocities, scattering modes etc. In particular, it has been become possible for the first time to derive an orthogonal system of functions that solves the transfer equation for plane media, to model numerically radiation fields in arbitrarily shaped 3D configurations with a prescribed accuracy, and to obtain general quadrature solutions for spheres with relativistic velocities. The latter are of special importance since they lead to accurate and convenient expressions for the diffusion limit in moving media. In this contribution the new techniques are reviewed and the consequences for our understanding of radiation fields briefly discussed.